Digital Readiness and Tax System Usability: A Structural Framework for MSME Compliance in Emerging Economies - Anggraeni, Windi Ariesti (Yayasan Sinergi Kawula Muda, 2025)
Indonesia has accelerated its digital tax transformation to improve MSME compliance through platforms such as e-Faktur and e-Filing. However, national compliance remains low at only 15–18%, with rural areas showing the weakest participation (Directorate General of Taxes, 2024). This study examines the structural barriers and readiness factors influencing digital tax compliance using the Information Systems Success Model (ISSM) and the Technology Acceptance Model (TAM). Employing a mixed-method approach with secondary national and international data, the study identifies key disparities in infrastructure, digital literacy, and system usability. Findings reveal that MSMEs in rural regions struggle with poor internet access, limited device ownership, and low digital and tax literacy. Complicated user interfaces—such as multi-step verification, unclear error messages, and inconsistent data fields—further hinder adoption. The analysis highlights that digital readiness, encompassing infrastructure, user competence, and interface design, is pivotal in shaping tax compliance behavior. Evidence from comparable countries shows that simplified interfaces, multilingual access, and continuous education can significantly improve compliance. This study proposes a readiness-based evaluation model for public digital systems and provides policy recommendations emphasizing infrastructure development, user-friendly system design, and contextualized capacity-building to close the MSME tax compliance gap.